Epithelial–mesenchymal transition in oral squamous cell carcinoma: An insight into molecular mechanisms and clinical implications - Jayanthi, P (J Oral Maxillofac Pathol, 2020)
Epithelial–mesenchymal transition (EMT) is an important event in embryonic development, fibrosis and cancer invasion. During cancer progression, the activation of EMT permits cancer cells to acquire migratory, invasive and stem-like properties. Despite recent advances in treatment, there is no improvement in the 5-year overall survival rate of oral squamous cell carcinoma (OSCC). Local recurrence and lymph node metastasis are considered to be mainly responsible for the low survival rate in OSCC. EMT plays a major role in local recurrence and lymph node metastasis of oral cancer. This review article addresses the clinical implications of EMT in OSCC and explains the molecular mechanisms of EMT, highlighting the cadherin switching and signaling pathways involved.